2022
DOI: 10.2147/jpr.s333454
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Alleviates the Chronic Pain of Osteoarthritis by Modulating NMDA Receptors in Midbrain Periaqueductal Gray in Rats

Abstract: Purpose Osteoarthritis (OA) is the most common cause to lead to chronic pain. Transcranial direct current stimulation (tDCS) has been widely used to treat nerve disorders and chronic pain. The benefits of tDCS for chronic pain are apparent, but its analgesic mechanism is still unclear. This study observed the analgesic effects of tDCS on OA-induced chronic pain and the changes of NMDA receptor levels in PAG after tDCS treatment in rats to explore the analgesic mechanism of tDCS. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…More and more studies believed that tDCS could be effective in the direct contact area of the electrode and play a role in the distance 38,39 . In our previous study, we chose M1 as the stimulation site of tDCS and observed the changes of NMDA receptor in periaqueductal gray (PAG) 24 . It is believed that the stimulation of tDCS in M1 region can activate contiguous regions such as PAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies believed that tDCS could be effective in the direct contact area of the electrode and play a role in the distance 38,39 . In our previous study, we chose M1 as the stimulation site of tDCS and observed the changes of NMDA receptor in periaqueductal gray (PAG) 24 . It is believed that the stimulation of tDCS in M1 region can activate contiguous regions such as PAG.…”
Section: Discussionmentioning
confidence: 99%
“…This exogenous stimulus may use similar pathways involved in the top-down modulation found across sensory systems 23 . In our previous study, we demonstrated that tDCS can alleviate OA-induced chronic pain in rats by modulating the expression of NMDA receptors in PAG to play an analgesic role 24 . However, whether the analgesic effect of tDCS can work in the spinal cord by top-down modulation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant animal experiments also partially confirmed the findings. Researchers established a chronic pain model by injecting a drug into the ankle joint of the rat and found that tDCS effectively restored mechanical allodynia and thermal hyperalgesia and its effects lasted two weeks [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial direct current stimulation can induce neuroplasticity in a manner dependent on N-methyl-D-aspartate receptors (NMDARs) ( Liebetanz et al, 2002 ; Nitsche et al, 2003 ), which can regulate signaling pathways by allowing positively charged ions, such as calcium, to enter the cell and strengthen the synapse. Research also discovered that tDCS increased the amount of NMDA receptors and subsequently enhanced pain-related responses in animals ( Li et al, 2022a , b ). This suggests tDCS enhances NMDAR-mediated synaptic plasticity by increasing neuronal membrane NMDAR density, heightening synaptic responsiveness crucial to modulating pain.…”
Section: Mechanisms Of Tdcs For Fibromyalgia Syndromementioning
confidence: 99%